Some Remarks About the Workers’ Motherhood in the Industrial City of Łódź in the 19th–20th Centuries - Śmiechowski, Kamil (Studia Historiae Oeconomicae, 2023)
Łódź, the so-called “Polish Manchester”, was the biggest textile center in the Eastern Europe, which developed in the 19th century and experienced all dramatic changes that happened in Poland during the long 20th century. As the vanguard of modernity, this industrial city was the place when all the pros and cons of the early capitalism appeared in much more dramatic way then elsewhere in Poland. In a result the problem such as workers motherhood and child labor became the real social phenomenon that forced many journalists, medical doctors, factory inspector and political activists to work against them. In this article, the way in which the workers motherhood and child labor was problematized in the discourse of Łódź is analyzed as the struggle with modernity. In author’s opinion, the experience of living in the industrial cities cause that approach to such complicated social problems developed in places like Łódź is less ideological and more empathizing then nationwide one. The specific case of Łódź can be useful in refreshing the Polish debate about modernity.